Efektivitas Konseling dengan Pendekatan Client Centred Therapy untuk Meningkatkan Kemandirian Siswa dalam Belajar - Ridha, Andi Ahmad; Idham, Azmul Fuady (INSIGHT: JURNAL PEMIKIRAN DAN PENELITIAN PSIKOLOGI, 2020)
This study aims to determine the effectiveness of counselling with a client-centred therapy approach to increase students' independence in learning. The subject in this study is one person, namely a 17-year-old male student who experiences independence in carrying out learning activities at school. This study used a single-case experimental design method with treatment in the form of counselling with a client-centred therapy approach to a class XI Vocational School student who experiences independence in learning. The research instrument was an independent observation checklist. Data were analyzed descriptively by describing the changes experienced by the subject before and after being given counselling. The results showed that the subjects were slow to show changes after attending nine counselling sessions. Subjects can express commitment to carrying out strategies to increase the subject's learning independence. But in practice, the subject is not persistent in implementing the agreed-upon strategies so that the subject shows less success in behaving independently after participating in a counselling program with a client centred therapy approach.